Proton-modified perovskite ceramic chip catalyst as well as preparation method and application thereof

By modifying the perovskite ceramic sheet catalyst by protons, the problems of the low efficiency of existing perovskite photocatalysts in photocatalytic decomposition of water and limited reaction scenarios are solved, and efficient hydrogen production reaction and application scenarios are achieved.

CN119455961APending Publication Date: 2025-02-18NORTHWEST ELECTROMECHANICAL ENG RES INST
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411436094.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

When existing perovskite photocatalytic decomposition of water to produce hydrogen, there are problems such as few catalyst active sites, high degree of photogenerating carrier recombination, low hydrogen production efficiency, and limited reaction scenarios.

Method used

The perovskite ceramic sheet catalyst is used to modify the protonation treatment in an acidic environment to remove the A-position ions of the perovskite oxide material and expose the B-position metal oxide, thereby changing its energy band structure and electron cluster density. Improve catalytic efficiency.

Benefits of technology

It realizes efficient hydrogen production reaction in the photo-piezoelectric coupling field, improves the catalytic activity and stability of the catalyst, and broadens the application scenarios of catalytic reactions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119455961A_ABST
    Figure CN119455961A_ABST
Patent Text Reader

Abstract

The invention discloses a proton-modified perovskite ceramic chip catalyst as well as a preparation method and application thereof. The preparation method comprises the following steps: dissolving lanthanum salt and nickel salt in a solution, adding a complexing agent, stirring and reacting to obtain precursor gel, drying the precursor gel, and calcining to obtain perovskite nano-powder; pressing the perovskite nano powder under uniaxial pressure, and performing high-temperature calcination to obtain a perovskite ceramic wafer; and putting the perovskite ceramic chip into an acid solution for protonation treatment, and then washing and drying to obtain the proton modified perovskite ceramic chip catalyst. According to the invention, on the basis of adopting the piezoelectric electro-catalyst, the catalytic efficiency of the piezoelectric electro-catalyst is comprehensively coordinated and improved by combining the preparation of the porous perovskite ceramic chip with protonation, the efficient hydrogen production reaction in a photo-piezoelectric coupling field is realized, the application scene of the catalytic reaction is effectively widened, and the preparation method has important environmental protection significance and economic value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of energy materials, and specifically relates to a proton-modified perovskite ceramic sheet catalyst and a preparation method and application thereof. Background Art

[0002] In recent years, with the decline of crude oil reserves and human dependence on fossil fuels causing many severe environmental problems such as greenhouse effect and acid rain, it is urgent to develop new high-efficiency green renewable energy production technology. Green energy includes hydropower, wind power, solar energy, hydrogen energy, bioenergy (biogas), geothermal energy (including ground source and water source) and tidal energy. Among them, solar energy is clean, pollution-free and inexhaustible. The effective use of solar energy has become one of the effective means to solve environmental and energy pressures. In addition, compared with any known non-renewable hydrocarbon fuel, hydrogen has a higher energy content per unit mass (120.7kJ / g) and is considered to be a green renewable energy with great potential. How to couple solar energy, hydrogen energy and water to form a low-energy, pollution-free green energy conversion system is an urgent problem to achieve carbon cycle. In recent years, researchers from various countries have successively started the study of "artificial photosynthesis" (i.e. photocatalysis), using catalysts to convert water into hydrogen, oxygen or highly economical compounds under the action of sunlight. Because photocatalytic technology uses clean solar energy to convert it into chemical energy, it takes into account energy, environmental and economic requirements and is currently considered the most promising technology for hydrogen production.

[0003] Piezoelectric semiconductor materials can control the size of their built-in electric field by applying external mechanical force or temperature, and at the same time control the polarization direction and amplitude inside the material, and adjust the local band bending degree of the interface of the piezoelectric reaction species, thereby achieving dynamic control of surface properties and catalytic redox reactions. Researchers have found that the band structure of many piezoelectric semiconductor materials matches the reduction / oxidation potential of hydrogen / water, and their piezoelectric effect or spontaneous polarization effect can be coupled with the photocatalytic effect, promoting the rapid migration of electrons and holes, extending their lifespan, and improving the efficiency of photocatalytic hydrogen production of piezoelectric semiconductor materials.

[0004] The current perovskite photocatalyst is only suitable for the photocatalytic conversion of powder samples and is limited by a wide band gap and a narrow range of light absorption wavelengths. If it is directly applied to the photocatalytic decomposition of water to produce hydrogen, it will produce a series of problems such as few catalyst active sites, high degree of photogenerated carrier recombination, low hydrogen production efficiency, and limited reaction scenarios. The present invention, based on the use of piezoelectric photocatalysts, prepares porous perovskite ceramic sheets in combination with protonation, comprehensively coordinates and improves the catalytic efficiency of piezoelectric photocatalysts, realizes efficient hydrogen production reactions in light-piezoelectric coupling fields, and effectively broadens the application scenarios of catalytic reactions, which has important environmental significance and economic value. Summary of the invention

[0005] The present invention aims at the defects of the existing photocatalytic technology based on perovskite oxide materials, such as poor catalytic hydrogen production efficiency, insufficient number of reaction active sites, and serious recombination of photogenerated carriers. A method for preparing a proton-modified perovskite ceramic sheet catalyst is provided. The unstable property of the Ruddlesden-Popper phase perovskite rock salt layer in an acidic environment is utilized, and the multi-physical field of light radiation and ultrasonic vibration is organically integrated to obtain a sheet ceramic photocatalyst with excellent catalytic activity and stability.

[0006] The technical purpose of the present invention is achieved through the following technical solutions:

[0007] A method for preparing a proton-modified perovskite ceramic sheet catalyst comprises the following steps:

[0008] Step 1: dissolving lanthanum salt and nickel salt in a solution, adding a complexing agent to obtain a mixed solution, adjusting the pH value of the mixed solution and stirring to obtain a precursor gel, and then drying and calcining the precursor gel to obtain perovskite nanopowder;

[0009] Step S2: pressing the perovskite nanopowder under uniaxial pressure and calcining at high temperature to obtain a perovskite ceramic sheet;

[0010] Step S3: placing the perovskite ceramic sheet in an acid solution for protonation treatment, followed by washing and drying to obtain a proton-modified perovskite ceramic sheet catalyst.

[0011] In perovskite, the AO bond is longer than the BO bond and has a higher surface energy, so the AO bond is more easily corroded. Currently, the protonation treatment method is used to remove the A-site ions of the perovskite oxide material, so that the B-site metal oxide is exposed on the outermost layer of the catalyst surface to change its energy band structure and electron group density, but there is still little research on related work. 2 NiO 4 As a perovskite oxide, the obtained powder is pressed under uniaxial pressure and then calcined at high temperature to obtain a perovskite ceramic sheet, which is then placed in an inorganic acid solution for protonation treatment. The protonation process can selectively remove La 2 NiO 4 The La ions at the end points of the perovskite fully expose the Ni ion sites at the reaction active center, which can effectively change the electronic structure and coordination environment of the catalyst and thus increase the redox reaction rate of the reaction system.

[0012] The lanthanum salt is a soluble lanthanum nitrate salt; the nickel salt is a soluble nickel nitrate salt. The solution includes at least one of a dilute nitric acid solution, an ammonia solution and deionized water.

[0013] The molar ratio of the lanthanum salt, the nickel salt and the complexing agent is 2:1:1.5-3; preferably, the molar ratio of the lanthanum salt, the nickel salt and the complexing agent is 2:1:2, at which the complexing effect is best when the ions are fully dispersed.

[0014] The complexing agent includes any one of citric acid and ethylenediaminetetraacetic acid; preferably, the complexing agent is citric acid.

[0015] Preferably, the solution is a dilute nitric acid solution and ammonia water is used to adjust the pH value of the mixed solution to 8 to 12, preferably, the pH value is adjusted to 8. The alkaline coordination environment helps the perovskite oxide powder to have a smaller particle size and higher reactivity.

[0016] The calcination temperature of the powder is 900-1200°C; preferably, the calcination temperature is 900°C. The calcination time is 4-8 hours; preferably, the calcination time is 6 hours; the heating rate is 1-5°C·min -1 ; Cooling rate is 1~5℃·min -1 Preferably, the heating rate is 2°C·min -1 ; The cooling rate is 5℃·min -1 Under this calcination environment, the crystal structure of the nanoparticles is complete, and the catalytic performance of the catalyst is stable and excellent.

[0017] The ceramic sheet can be a dense ceramic sheet or a porous ceramic sheet with 5-20wt% starch added as a pore-forming agent. Preferably, the porous ceramic sheet with 15wt% starch as a pore-forming agent has a rich combination of pore structures such as micropores, mesopores and macropores, which can provide multiple channels for the full interaction between the reaction solution and the catalyst. The reaction solution can not only contact the outer surface of the catalyst, but also have full contact with the inner surface of the catalyst pores, thereby improving the adsorption efficiency of protons in the solution at the active sites on the sample surface.

[0018] The uniaxial pressure of the obtained ceramic sheet is 8-15 MPa; preferably, the uniaxial pressure of 12 MPa is used to obtain a 15 mm diameter embryo with a complete morphology and good shrinkage during calcination.

[0019] The calcination temperature of the ceramic sheet is 1300-1400°C; preferably, the calcination temperature is 1400°C. The calcination time is 6-8 hours; preferably, the calcination time is 8 hours. The heating rate is 1-5°C·min -1 ; Cooling rate is 1~5℃·min -1 Preferably, the heating rate is 4°C·min -1 ; The cooling rate is 3℃·min -1 The ceramic sheet calcined under this calcination environment has a complete crystal structure, clear grain boundaries, and good mechanical properties, catalytic activity and chemical stability.

[0020] The acid solution is an inorganic acid, including any one of nitric acid, sulfuric acid and hydrochloric acid; preferably, hydrochloric acid is selected to prepare the acid solution.

[0021] It is further preferred that the proton concentration in the hydrochloric acid be 0.006 mol·L -1 ;; The protonation time is 4 hours. The proton concentration and treatment time determine the protonation degree of the porous ceramic sheet, that is, the degree of change in the structure and surface charge of the porous ceramic sheet. Under this concentration and time, the catalytic activity of the obtained catalyst is better.

[0022] The present invention adopts piezoelectric photocatalytic reaction technology, and changes the grain size, specific surface area, energy band structure and surface charge of the catalytic reaction by adjusting the proton concentration, reaction time, phase preparation conditions, and mass fraction of the pore-forming agent in the prepared solution, so as to make full use of the perovskite oxide La 2 NiO 4 The optical response and piezoelectric response of the system can realize the optimization of multi-field coupling energy conversion and expand the application scenarios. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The protonated porous La provided in the embodiment of the present invention 2 NiO 4 Flow chart of the preparation of ceramic sheets.

[0024] Figure 2a The perovskite oxide La provided in the embodiment of the present invention 2 NiO 4 SEM image of nanopowder.

[0025] Figure 2b This is a cross-sectional SEM image of a perovskite ceramic sheet after adding a pore-forming agent and undergoing protonation treatment according to an embodiment of the present invention.

[0026] Figure 2c This is a surface SEM image of a perovskite ceramic sheet after adding a pore-forming agent and undergoing protonation treatment provided in an embodiment of the present invention.

[0027] Figure 3 The perovskite oxide La provided in the embodiment of the present invention 2 NiO 4 XRD spectra of nanopowders after treatment in different proton concentrations.

[0028] Figure 4 This is a pore size distribution diagram of the perovskite ceramic sheet provided in an embodiment of the present invention.

[0029] Figure 5 This is a diagram showing the Zeta potential change of the perovskite ceramic sheet provided in an embodiment of the present invention.

[0030] Figure 6 It is a curve diagram showing the change of hydrogen production over time in a photo-piezoelectric coupling field of a perovskite ceramic sheet provided in an embodiment of the present invention. DETAILED DESCRIPTION

[0031] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings of specific embodiments.

[0032] The present application utilizes piezoelectric semiconductor photocatalysts and mechanical energy and solar energy to catalyze water decomposition and hydrogen production technology, which adopts a green and sustainable energy chemical conversion method. The piezoelectric photocatalytic hydrogen production technology utilizes piezoelectric semiconductor materials with suitable energy band structures to convert absorbed photons into photoexcitons, which are separated into carriers (i.e., electrons and holes). The electrons and holes are respectively transmitted to the surface of the catalyst, and undergo reduction and oxidation reactions with water to generate hydrogen, oxygen, hydrogen peroxide, etc. At the same time, under the action of external mechanical forces, the size of the built-in electric field can be formed inside the piezoelectric semiconductor material, and the external electric field can control the direction and amplitude of polarization, adjust the local energy band bending degree of the interface of the piezoelectric reaction species, and realize the dynamic control of surface properties and catalytic redox reactions; the polarization effect contained in the piezoelectric semiconductor material can be coupled with the photocatalytic effect, which promotes the rapid migration of electrons and holes, prolongs their life, and improves the photocatalytic hydrogen production efficiency of the piezoelectric semiconductor material.

[0033] The catalytic system of the present invention for protonating the catalyst based on piezoelectric photocatalytic technology is a multiphase system, which utilizes piezoelectric photocatalytic decomposition of water to produce hydrogen. The catalytic reaction occurs at the gas-liquid-solid three-phase interface of hydrogen, water and catalyst. Protonation can be used to achieve and enhance the interaction ability of the three-phase interface and change the electronic structure and charge distribution of the catalyst surface, thereby improving the catalytic efficiency of the system.

[0034] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with embodiments. The specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention.

[0035] Example 1

[0036] Preparation of La by improved citrate method 2 NiO 4 Powder.

[0037] 216.5 g La(NO 3 ) 3 6H 2 O and 72.7 g Ni (NO3 ) 2 6H 2 O was dissolved in 200 ml of deionized water, and 96.1 g of citric acid as a complexing agent was gradually added during stirring. The pH value was adjusted to 8 by ammonia water to keep it stable. The solution was continued to be heated to 80 °C in a water bath and magnetically stirred for 6 hours until it became a thick blue precursor gel. It was then dried in an oven for 3 hours and a gray precursor powder was obtained by pre-calcination. Finally, the precursor powder was calcined in a muffle furnace at 900 °C for 6 hours, and the heating rate was selected to be 2 °C·min -1 The cooling rate is 5℃·min -1 , to obtain pure phase perovskite oxide La 2 NiO 4 Nano powder.

[0038] Perovskite oxide La 2 NiO 4 The morphology of nanopowders is Figure 2a As shown in the SEM image in the middle, the grain surface is smooth and no impurity phase is formed.

[0039] Comparative Example 1

[0040] Preparation of La by sol-gel method 2 NiO 4 Powder.

[0041] 162.9 g La 2 O 3 and 18.7 g NiO were dissolved in 200 ml dilute nitric acid and stirred continuously until the solution was clear. 96.1 g citric acid complexing agent was gradually added during stirring. The pH value of the solution was then adjusted to 8 with ammonia water to ensure that the powder had high activity. Then, it was stirred in a 90°C oil bath until a blue gel was formed. The blue gel was taken out and ignited in an electric furnace to produce a gray-black precursor powder. The precursor powder was calcined at 1000°C for 6 hours, and the heating rate was 2°C·min -1 The cooling rate is 5℃·min -1 , to obtain pure phase perovskite oxide La 2 NiO 4 Nano powder.

[0042] Comparative Example 2

[0043] Preparation of La by solid phase reaction method 2 NiO 4 Powder.

[0044] 162.9 g La 2 O 3and 18.7 g NiO were dispersed in 400 ml ethanol and ground by a planetary ball mill for 48 h. The powder sample was then dried in an oven at 70 °C and calcined in a muffle furnace at 1200 °C for 6 h. The heating rate was 2 °C min -1 ; The cooling rate is 5℃·min -1 The calcined powder was dispersed in 400 ml of ethanol and ground in a planetary ball mill for 48 hours. The powder sample was dried in a 70°C oven and then calcined again in a muffle furnace at 1200°C for 6 hours. The heating rate was also 2°C min. -1 The cooling rate is also 5℃·min -1 , to obtain pure phase perovskite oxide La 2 NiO 4 Nano powder.

[0045] Example 2

[0046] Bulk porous La was prepared by uniaxial pressure combined with high temperature sintering. 2 NiO 4 Ceramic pieces.

[0047] 220 g of perovskite oxide La 2 NiO 4 The nanopowder and 38.8 g of starch pore former were fully ground in an agate mortar for 30 minutes and then evenly filled into a 15 mm MJ series ordinary cylindrical mold of Tianjin Keqi Co., Ltd. The 769YP-15A manual powder tablet press of Tianjin Keqi Co., Ltd. was used to press into a circular embryo with a diameter of 15 mm under a uniaxial pressure of 12 MPa. The prepared circular embryo was then sintered at 1400 ° C in an air atmosphere for 8 hours, and the heating rate was selected to be 4 ° C·min -1 The cooling rate is 3℃·min -1 .

[0048] The prepared porous La 2 NiO 4 The XRD spectrum of the ceramic sheet is as follows: Figure 3 As shown, the phase structure of the sample is complete and no impurities are produced.

[0049] Bulk porous La 2 NiO 4 The pore size distribution of the ceramic sheet is as follows Figure 4 As shown, there is little difference in pore size distribution between the bulk ceramic sheet and the sintered dense ceramic sheet, which indicates that the dense surface structure of the ceramic sheet with added pore-forming agent makes a large amount of nitrogen adsorbed on the sample surface, while the components that actually enter the internal pore structure are limited.

[0050] Bulk porous La 2 NiO 4The Zeta point of the ceramic sheet is as follows: Figure 5 As shown in the figure, the Zeta potential test confirmed the change of proton adsorption on the sample surface. 2 NiO 4 The surface of the ceramic sheet is negatively charged in aqueous solution, which is not conducive to the accumulation of protons on the catalyst surface and the reduction reaction during the hydrogen production reaction.

[0051] Bulk porous La 2 NiO 4 The hydrogen production activity of the ceramic sheet in decomposing deionized water under the conditions of photo-piezoelectric coupling reaction is shown in Figure 6 As shown, 3994.44 μmol·m -2 ·h -1 The hydrogen production activity indicates that in the high-frequency vibration piezoelectric field, part of the reaction solution still enters the internal pores and quickly flushes the internal channels under the high-frequency vibration of ultrasound.

[0052] Example 3

[0053] Protonated porous La was prepared by uniaxial pressure combined with high temperature sintering and protonation treatment. 2 NiO 4 Ceramic pieces.

[0054] 220 g of perovskite oxide La 2 NiO 4 The nanopowder and 38.8 g of starch pore former were fully ground in an agate mortar for 30 minutes and then evenly filled into a 15 mm MJ series ordinary cylindrical mold of Tianjin Keqi Co., Ltd. The 769YP-15A manual powder tablet press of Tianjin Keqi Co., Ltd. was used to press into a circular embryo with a diameter of 15 mm under a uniaxial pressure of 12 MPa. The prepared circular embryo was then sintered at 1400 ° C in an air atmosphere for 8 hours, and the heating rate was selected to be 4 ° C·min -1 The cooling rate is 3℃·min -1 .

[0055] The sintered ceramic sheet was placed in a beaker containing 80 ml of deionized water, and 40 μl of HCl was gradually added and magnetically stirred for 12 hours. Finally, the ceramic sheet was ultrasonically cleaned in a beaker containing 100 ml of deionized water until it was neutral, and then dried in an oven at 80 °C to obtain protonated porous La 2 NiO 4 Ceramic sheet. Protonated porous La 2 NiO 4 The preparation flow chart of ceramic sheets is as follows: Figure 1 shown.

[0056] The protonated porous La 2NiO 4 The cross-sectional morphology of the ceramic sheet is as follows Figure 2b As shown in the SEM image, the surface morphology is Figure 2c As shown in the SEM image in the figure, the cross section representing the bulk phase has a large number of pore structures, and a certain amount of pore channels caused by protonation also appear on the surface. This increases the specific surface area of ​​the catalyst and helps the reaction solution quickly enter the internal pores from the sample surface.

[0057] The protonated porous La 2 NiO 4 The XRD spectrum of the ceramic sheet is as follows: Figure 3 As shown, the phase structure of the sample is complete and no impurities are produced.

[0058] Protonated porous La 2 NiO 4 The pore size distribution of the ceramic sheet is as follows Figure 4 As shown, the surface of the ceramic sheet treated with hydrochloric acid protonation produced a texturing and pore-forming effect, which effectively increased the pathway for reactants to enter the internal pores of the sample, and a macroporous structure with a pore size of more than 400 nm appeared. The richer composition of different pore sizes can effectively increase the mass transfer rate of the reaction system.

[0059] Protonated porous La 2 NiO 4 The Zeta point of the ceramic sheet is as follows: Figure 5 As shown in the figure, when the porous ceramic sheet is filled with 0.006 mol·L -1 After treatment with the proton solution, the catalyst surface was adsorbed by protons and gradually became positively charged, and the surface Zeta potential increased to 15.3 mV. It can be clearly confirmed that the protonation process leads to the introduction of protons into La 2 NiO 4 inside the structure and on the surface of the sample, thereby causing the accumulation of positive charges on the surface of the sample.

[0060] Protonated porous La 2 NiO 4 The hydrogen production activity of the ceramic sheet in decomposing deionized water under the conditions of photo-piezoelectric coupling reaction is shown in Figure 6 As shown in Figure 2, a large amount of reaction solution quickly poured into the pore structure inside the ceramic and fully reacted with the internal surface of the pores under the piezoelectric effect, further increasing the hydrogen production activity to 7603.75 μmol·m -2 ·h -1 .

[0061] Comparative Example 3

[0062] Dense La was prepared by uniaxial pressure combined with high temperature sintering. 2 NiO 4 Ceramic pieces.

[0063] 220 g of perovskite oxide La 2 NiO 4 The nanopowder was evenly filled into the MJ series Ф15 ordinary cylindrical mold of Tianjin Keqi Co., Ltd., and pressed into a circular embryo with a diameter of 15 mm under a uniaxial pressure of 12 MPa using the 769YP-15A manual powder tablet press of Tianjin Keqi Co., Ltd. Then the prepared circular embryo was sintered at 1400℃ in air atmosphere for 8 hours, and the heating rate was 4℃·min -1 The cooling rate is 3℃·min -1 .

[0064] Dense La 2 NiO 4 The pore size distribution of the ceramic sheet is as follows Figure 4 As shown, due to the dense surface structure, the pore structure of the dense ceramic sheet is distributed below 400 nm.

[0065] Dense La 2 NiO 4 The hydrogen production activity of the ceramic sheet in decomposing deionized water under the conditions of photo-piezoelectric coupling reaction is shown in Figure 6 As shown in Figure 2, the dense structure limits the contact area between the catalyst surface and water, resulting in a catalytic hydrogen production activity of only 1310.97 μmol·m -2 ·h -1 .

[0066] Comparative Example 4

[0067] Bulk porous La was prepared by uniaxial pressure combined with high temperature sintering and 43 μl protonation treatment. 2 NiO 4 Ceramic pieces.

[0068] 220 g of perovskite oxide La 2 NiO 4 The nanopowder and 38.8 g of starch pore former were fully ground in an agate mortar for 30 minutes and then evenly filled into a 15 mm MJ series ordinary cylindrical mold of Tianjin Keqi Co., Ltd. The 769YP-15A manual powder tablet press of Tianjin Keqi Co., Ltd. was used to press into a circular embryo with a diameter of 15 mm under a uniaxial pressure of 12 MPa. The prepared circular embryo was then sintered at 1400 ° C in an air atmosphere for 8 hours, and the heating rate was selected to be 4 ° C·min -1 The cooling rate is 3℃·min -1 .

[0069] The sintered ceramic sheet was placed in a beaker containing 80 ml of deionized water, and 43 μl of HCl was gradually added and magnetically stirred for 12 hours. Finally, the ceramic sheet was ultrasonically cleaned in a beaker containing 100 ml of deionized water until it was neutral, and then dried in an oven at 80 °C to obtain protonated porous La 2 NiO 4 Ceramic pieces.

[0070] Protonated porous La 2 NiO 4 The XRD spectrum of the ceramic sheet is as follows: Figure 3 As shown in the figure, when the proton concentration in the solution exceeds 0.006 mol·L -1 The phase structure of the sample is no longer complete.

[0071] In summary, it can be concluded that the proton-modified perovskite ceramic sheet catalyst of the present invention has the following beneficial effects compared with the prior art:

[0072] First, the present invention proposes a proton-modified perovskite ceramic sheet catalyst and a preparation method and application thereof. The proton-modified perovskite ceramic sheet catalyst effectively couples multiple physical fields such as light radiation and mechanical vibration, and effectively suppresses the rate of recombination of photogenerated carriers.

[0073] Second, the proton-modified perovskite ceramic sheet catalyst proposed in the present invention effectively improves the interaction ability between the reaction solution and the catalyst pores by means of protonation, and fully flushes the catalyst surface and pores under the action of high-frequency ultrasound, thereby greatly improving the photo-piezoelectric coupled hydrogen production activity.

[0074] Third, the proton-modified perovskite ceramic sheet catalyst proposed in the present invention can be applied to hydropower hydrogen production projects, offshore hydrogen production projects, etc.; compared with existing powder photocatalysis, it has a wider range of applications.

[0075] In particular, the proton-modified La 2 NiO 4 Perovskite ceramic sheet catalysts have the characteristics of soft ferrites and can be effectively recycled after engineering operations.

[0076] It should be noted that the above-described embodiments are only preferred embodiments of the present invention. For those skilled in the art, without departing from the principles of the present invention, the present invention may be modified, improved and replaced with equivalents, and these modifications, improvements and equivalent replacements are also considered to fall within the scope of protection of the claims of the present invention.

Claims

1. A method for preparing a proton-modified perovskite ceramic sheet catalyst, characterized in that: The steps include: S1: dissolving lanthanum salt and nickel salt in a solution, adding a complexing agent thereto to obtain a mixed solution, adjusting the pH value of the mixed solution and stirring to obtain a precursor gel, and then drying and calcining the precursor gel to obtain perovskite nanopowder; S2: pressing the perovskite nanopowder under uniaxial pressure and calcining at high temperature to obtain a perovskite ceramic sheet; S3: placing the perovskite ceramic sheet in an acid solution for protonation treatment, and then washing and drying to obtain the proton-modified perovskite ceramic sheet catalyst.

2. The method for preparing a proton-modified perovskite ceramic sheet catalyst according to claim 1, characterized in that: In step S1, the lanthanum salt is a soluble lanthanum nitrate salt; the nickel salt is a soluble nickel nitrate salt; the complexing agent includes any one of citric acid and ethylenediaminetetraacetic acid; and the solution includes at least one of a dilute nitric acid solution, an ammonia solution and deionized water.

3. The method for preparing the proton-modified perovskite ceramic sheet catalyst according to claim 1, characterized in that: In the step S1, the pH value of the mixed solution is adjusted to 8 to 12.

4. The method for preparing a proton-modified perovskite ceramic sheet catalyst according to claim 1, characterized in that: In the step S1, the molar ratio of the lanthanum salt, the nickel salt and the complexing agent is 2:1:1.5-3.

5. The method for preparing a proton-modified perovskite ceramic sheet catalyst according to claim 1, characterized in that: In step S1, the calcination temperature is 900-1200°C; the calcination time is 4-8 hours; the heating rate is 1-5°C·min -1 ; Cooling rate is 1~5℃·min -1 .

6. The method for preparing a proton-modified perovskite ceramic sheet catalyst according to claim 1, characterized in that: In step S2, the calcination temperature is 1300-1400°C; the calcination time is 6-8 hours; the heating rate is 1-5°C·min -1 ; Cooling rate is 1~5℃·min -1 .

7. The method for preparing a proton-modified perovskite ceramic sheet catalyst according to claim 1, characterized in that: In step S3, the acid solution is an inorganic acid, and the inorganic acid includes any one of nitric acid, sulfuric acid, and hydrochloric acid.

8. The method for preparing the proton-modified perovskite ceramic sheet catalyst according to claim 7, characterized in that: In step S3, the proton concentration in the inorganic acid is 0.001 to 0.006 mol·L -1 ; The protonation time is 0.5 to 6 hours.

9. A proton-modified perovskite ceramic sheet catalyst prepared according to the preparation method according to any one of claims 1 to 8.

10. The use of the proton-modified perovskite ceramic sheet catalyst according to claim 1 in a water decomposition hydrogen production reaction in a photo-piezoelectric coupled reaction field, characterized in that: The following steps are followed: first, a catalyst and a reaction solution are added to a hydrogen production reaction bottle, and the oxygen in the hydrogen production reaction device is purged and emptied by an inert gas such as nitrogen or argon; then, the hydrogen production reaction bottle is fixed in an ultrasonic cleaning machine with an adjustable power range of 70 to 100 W as a pressure source; under the action of water wave vibration in the ultrasonic cleaning machine, the surface of the proton-modified perovskite ceramic sheet catalyst is subjected to pressure; then, a single-sided irradiated xenon lamp is fixed above the ultrasonic cleaning machine as a light source; under the conditions of a photo-piezoelectric coupling reaction, the proton-modified perovskite ceramic sheet catalyst catalyzes a water decomposition reaction to generate hydrogen, oxygen, and hydrogen peroxide, and a sampler is used to pierce the rubber stopper on the top of the bottle to sample the product, and then a gas chromatograph is used to test and analyze the composition and content of the product.